PENDEKATAN SOCIO-CULTURAL DEVELOPMENT DAN SOCIO-POLITICAL INTERVENSION UNTUK MENGATASI KONFLIK SOSIAL SEBAGAI UPAYA MEMANTAPKAN KETAHANAN WILAYAH DI SURAKARTA - Rusnaini _ (Jurnal Ketahanan Nasional, 2013)
This paper explained the social conflict in Surakarta which showed in Christians and Muslims group conflict, residents’ conflict which brought into religious conflict, and often connected with security and order issues, and also the conflict of Javanese against Chinese and Arabic ethnic. The qualitative and quantitative data of this paper showed the conflict as covert social hatred which potentially developed into tense, and with the conflict trigger would create inter group violence. Therefore the socio-cultural development approach and socio-political intervention approach carried out by the Surakarta Local Government to built cross cutting affiliation and cross cutting loyalties among different identities had not yet maximum.Keywords: Social Conflict, Socio-cultural Development, Socio-Political Intervention, and Regional Resilience